Memória e patrimônio em Minas Gerais: o caso da Companhia Industrial Itaunense - Mariana Goncalves Moreira (2014)
Textile production in Minas Gerais has been practiced since the beginning of colonization. The manufacture of textiles, originally developed by hand in domestic units, was one of the first sectors to go through the process of industrialization in Minas Gerais, with the use of labor-wage labor, mechanization of production, separation between capital and labor, among others. In Itaúna, the Companhia Industrial Itaunense was implanted in 1911 and quickly acquired great economic and social importance. After its decommissioning, the plant filed for blasting, but still strongly present in the memory of the local population. Today, the remaining structures of Unidade I are one of the constituent elements which can be understood as Industrial Landscape, confirming the need to know, record and disseminate this heritage. That is the theme of this research work.